Software architecture : 10th European Conference, ECSA 2016, Copenhagen, Denmark, November 28-December 2, 2016, Proceedings /: 10th European Conference, ECSA 2016, Copenhagen, Denmark, November 28-December 2, 2016, Proceedings. (2016) - Unknown
No abstract available